Social outcomes of young adults with cerebral palsy. (September 2013) - Reddihough, Dinah S.; Jiang, Benran; Lanigan, Anna; Reid, Susan M.; Walstab, Janet E.; Davis, Elise
Abstract: Background Functional abilities and social outcomes of young adults with cerebral palsy (CP) are relatively underresearched. Improvements in paediatric care have extended the expectation of achieving adulthood to 90%. Method Young adults aged 20–30 years with CP ( n = 335) were compared to a population-based control group ( n = 2, 152) of the same age. Motor function, self-care abilities, educational level, and social outcomes were determined by questionnaire. Results Half the study group walked independently, but only 35.5% were independent in self-care. In comparison to their peers without disability, the study group's highest educational level was lower ( p < .0001), as were rates of employment (36.3% compared with 80%), they were more likely to be living with parents (80% compared with 21%), to be single, and to have limited financial resources. Conclusion Young adults with CP are functionally and socially disadvantaged in contrast with their peers without disability. Self-care dependence, intellectual disability, and communication impairments contribute to these outcomes but are not solely responsible.